Amplified drought induced by climate change reduces seedling emergence and increases seedling mortality for two Mediterranean perennial herbs. Issue 22 (10th November 2021) - Garnier, Suzon; Giordanengo, Emma; Saatkamp, Arne; Santonja, Mathieu; Reiter, Ilja M.; Orts, Jean‐Philippe; Gauquelin, Thierry; Meineri, Eric
Abstract: Seedling recruitment is a bottleneck for population dynamics and range shift. The vital rates linked to recruitment by seed are impacted by amplified drought induced by climate change. In the Mediterranean region, autumn and winter seedling emergence and mortality may have strong impact on the overall seedling recruitment. However, studies focusing on the temporal dynamic of recruitment during these seasons are rare. This study was performed in a deciduous Mediterranean oak forest located in southern France and quantifies the impact of amplified drought conditions on autumn and winter seedling emergence and seedling mortality rates of two herbaceous plant species with meso‐Mediterranean and supra‐Mediterranean distribution (respectively, Silene italica and Silene nutans ). Seedlings were followed from October 2019 to May 2020 in both undisturbed and disturbed plots where the litter and the aboveground biomass have been removed to create open microsites. Amplified drought conditions reduced seedling emergence and increased seedling mortality for both Silene species but these negative effects were dependent on soil disturbance conditions. Emergence of S. italica decreased only in undisturbed plots (−7%) whereas emergence of S .  nutans decreased only in disturbed plots (−10%) under amplified drought conditions. The seedling mortality rate of S .  italica was 51% higher under amplified drought conditions in undisturbed plots while that of S .  nutans was 38% higher in disturbed plots. Aridification due to lower precipitation in the Mediterranean region will negatively impact the seedling recruitment of these two Silene species. Climate change effects on early vital rates may likely have major negative impacts on the overall population dynamic. Abstract : This study was performed in a deciduous Mediterranean oak forest and quantifies the impact of amplified drought conditions on autumn and winter seedling emergence and seedling mortality rates of two Silene species. Amplified drought conditions reduced seedling emergence and increased seedling mortality for both Silene species but these negative effects were dependent on soil properties.